Effect of different packages of practices on organic leafy vegetable production - Tharani, B.; Sivachandiran, S.; Pradheeban, L.; Selvanathan, N. (Annual Research Session-2008, Vavuniya Campus, 2008)
In agriculture, Uses of inorganic chemicals are often criticized due to their adverse effect on human health and environment. Especially its effects on leafy vegetables are high as they often eat as raw or partially cooked forms. Considering the important of producing leafy vegetables with low inputs a study was conducted to find out the effect of different packages of practices on leafy vegetable production at Agricultural Research Station, Thirunelvely, Jaffna. Three popular leafy vegetables such as Alternantherasessilis (Ponnankani), Centellaasiatica (Valarai) and Amarathustricolor (Thampala- Keerai) were cultivated with eight treatment combinations which include organic pesticides, organic fertilizer and repellent crops. Higher yield and low pest incidence were recorded in treatment combination with recommended levels of fertilizer, neem spray and grown with repellent crop for all three crops. Anyhow, the yields are not statistically different among the treatment in Alternantherasessilis and Centellaasiaticathe yield of amaranthustricolor is significantly higher in treatment with recommended fertilizer application. The leaf stem ratio is high in treatment with organic fertilizer, neem extract spray and grown with repellent crop in all three plants. Less percentages of damage leaves was observed in neem extract and repellent crop treatment combinations in all three crops. Therefore, farmers can be advised to cultivate these three leafy vegetable crops with organic fertilizer, neem extract spray and repellent crop for the better quality, yield and also avoid adverse effects of chemicals on leafy vegetables.
Keywords: Organic; Pesticide; Fertilizer; Repellent